Pemberdayaan Kelompok Masyarakat dalam Pembuatan Persemaian Tendani (Goniothalamus Macrophyllus) di Desa Legokherang, Cilebak Kabupaten Kuningan - Adhya, Ilham; Supartono, Toto; Hendrayana, Yayan (Empowerment, 2022)
Efforts to preserve biodiversity, in this case Tendani (Goniothalamus macrophyllus) as a medicinal plant, are not only the responsibility of the manager of an area but also the responsibility of all of us, because collaborative efforts will provide maximum results. real efforts are needed, especially from the surrounding community to get to know the existing natural resources as well as efforts to preserve them through plant cultivation activities in nurseries, this activity is expected to increase awareness of the preservation of natural resources and improve the community's economy. The purpose of this activity is to preserve tendani, increase public knowledge about the benefits and cultivate tendani as medicinal plants